Seismic behavior of frames with weak bolted end plate connections rehabilitated by posttensioned tendons under near‐/far‐field earthquakes. (21st February 2020) - Saberi, Vahid; Saberi, Hamid; Gerami, Mohsen; Kheyroddin, Ali
Summary: Posttensioned tendons can be used for rehabilitation of frames as well as for providing self‐centering ability. The optimum selection of retrofit parameters is carried out based on their effect on the seismic behavior of a structure. The results of 2D numerical modeling of the frames in this paper revealed that the rehabilitation of a frame with weak end plate bolted connection by adding posttensioned tendons improves the seismic response of the weak frame to be close to that of the reference frame, whose connections are designed according to AISC code. It was observed that the roof displacements were reduced by 5%, and the maximum story drifts in near‐ and far‐field earthquakes were reduced by 8% and 2% in the rehabilitated frames on average compared to those of the reference frame. The results of 3D substructure numerical models, verified by experimental results, indicated that the changes in the tendon diameter from 12 to 18 mm increased the moment capacity and initial rotational stiffness by 38% and 60%, respectively, compared to those of the reference model. The increase in tendon distance from 18 to 22 cm resulted in 29% rise in moment capacity compared to that of the reference frame.